EXPERIMENTS ON THE PRODUCTION OF SPECIFIC ANTISERA FOR INFECTIONS OF UNKNOWN CAUSE : III. NEPHROTOXINS: THEIR SPECIFICITY AS DEMONSTRATED BY THE METHOD OF SELECTIVE ABSORPTION. - Wilson, George W. (The Rockefeller University Press, 1920)
As Pearce has shown, a serum highly injurious to the kidney of dogs can be produced by the immunization of rabbits with washed renal tissue of the dog. The histological findings are striking and characteristic, the most noteworthy being a glomerular lesion of special type. The renal changes differ much from those Pearce described. The injury to the kidney is not to be explained by hemolytic and hemagglutinative elements in the serum. The complete removal of such antibodies by exhaustion of the serum with successive portions of red cells fails to lessen materially its ability to cause kidney lesions. Furthermore, an ordinary hemolytic and hemagglutinative serum produced by the use of washed red cells as antigen fails to cause similar lesions. The distinctive, injurious principle of antikidney serum can be removed and the latter rendered innocuous by absorption with kidney tissue. To all practical intents and purposes it would seem that nephrotoxic serum of. the sort here described is specific. If infected tissue is to be utilized as an antigen for the production of therapeutic antisera the latter must in some instances be exhausted with tissue of the same sort prior to introduction into the animal body.